DAMPAK PENYULUHAN WAWASAN KEBANGSAAN TERHADAP PARTISIPASI PEMBANGUNAN MASYARAKAT DI DESA NGADIREJO, SALAMAN KABUPATEN MAGELANG - Rita Kuntarti; Tjatur Supriyono (JURNAL DWIJA KUSUMA, 2023)
The rise of the phenomenon of the decline of nationalism in Indonesian society in general and the people of Ngadirejo village where the majority of the population only have elementary school education (usually easily incited and sparked by issues). national insight in supporting environmental resilience. The method used is qualitative by collecting data through questionnaires that are filled out to village officials and the Ngadirejo village community. The results of this study are that first, the people and apparatus of Ngadirejo Village do not understand nationalism, especially those related to rights and obligations as citizens. Second, conveying knowledge about national insights and defending the country to the public can increase knowledge as well as a stimulant so that people understand better and can further increase nationalism and participate in development